Analysis of the factors affecting the application of critical thinking with the behavior of caring nurses in providing nursing care in RS Royal Prima Medan 2020 - ., Yusliana; Ginting, Chrismis Novalinda; Chiuman, Linda; Erawati, Suci (International Journal of Research in Medical Sciences, 2021)
Background: Caring behavior is the core in nursing that is indispensable in providing nursing care. One of the ways to improve caring behavior is through the development of critical thinking skills. This study was conducted to determine the effect of applying critical thinking with caring behavior of nurses in providing nursing care at the Royal Prima hospital in Medan. Methods: This study was a quantitative study using correlation research methods with a cross sectional approach to 35 nurses at the Royal Prima hospital in Medan using a simple random sampling technique. Results: The results showed that there was a significant influence between critical thinking and nurse caring behavior (p=0.020; 0.05), the characteristics of respondents who had an effect on nurse caring behavior were training (p=0.025; 0.05), critical thinking variable was a the most influential factor with nurses' caring behavior (OR=3.590). Conclusions: Based on the results of this study the importance of developing new knowledge and skills to improve critical thinking skills and caring behavior.